2012
DOI: 10.4049/jimmunol.1201818
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Suppression of Humoral Immunity by Anergic Ars/A1 B Cells

Abstract: Autoreactive anergic B lymphocytes are considered to be dangerous because of their potential for activation and recruitment into autoimmune responses. Yet they persist for days and constitute ~5% of the B cell pool. We assessed their functional potential in the Ars/A1 transgene model, where anergic B cells express a dual-reactive antigen receptor that binds, in addition to a self-antigen, the hapten p-azophenylarsonate (Ars). When Ars/A1 B cells were transferred into adoptive recipients that were immunized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…T cells, the literature is more limited on the topic of Breg specificity. Several studies have identified specific subpopulations of B cells as immunoregulators in contact hypersensitivity or autoimmunity models, which may require appropriate antigen recognition 9,13,[24][25][26]. The work reported herein, however, provides the most complete demonstration of recognition being required for allograft tolerance.…”
mentioning
confidence: 82%
“…T cells, the literature is more limited on the topic of Breg specificity. Several studies have identified specific subpopulations of B cells as immunoregulators in contact hypersensitivity or autoimmunity models, which may require appropriate antigen recognition 9,13,[24][25][26]. The work reported herein, however, provides the most complete demonstration of recognition being required for allograft tolerance.…”
mentioning
confidence: 82%
“…Europium (Eu 3+ )‐based fluoroimmunometric assays were described previously . For quantification of total IgG1κ produced in vivo, 96‐well europium plates (Greiner Bio‐One, Frickenhausen, Germany) were coated overnight at 4°C with rat antimouse kappa (RαMκ) (mAb 187.1, generated in‐house) followed by treatment with blocking buffer (2% BSA, 1% gelatin in PBS) for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Europium (Eu 3+ )-based fluoroimmunometric assays were described previously [58,59]. For quantification of total IgG1κ produced in vivo, 96-well europium plates (Greiner Bio-One, Frickenhausen, Germany) were coated overnight at 4 • C with rat antimouse kappa (RαMκ) (mAb 187.1, generated in-house) followed by treatment with blocking buffer (2% BSA, 1% gelatin in PBS) for 2 h at 37 • C. Serum samples were diluted in blocking buffer and incubated at 37 • C for 2 h or overnight at 4 • C. IgG1κ antibodies were detected using biotin-rat anti-mouse IgG1 (mAb RMG1-1, Biolegend), and quantities were interpolated based on standard binding curves generated using IgG1κ (MOPC 31C) myeloma Ig (Sigma-Aldrich, St. Louis, MO).…”
Section: Antibody Immunoassaysmentioning
confidence: 99%
“…Recently, Cahalan and colleagues [44] showed that naïve antigen-expressing B cells and antigen-specific T cells formed stable conjugates as early as 72 h after adoptive transfer, but this time point does not preclude the possibility that T cells had already been primed on B-cell-derived antigen presented by DCs. Wysocki and colleagues [8] showed that self-antigen-specific anergic B cells can induce tolerance, and that this was partially dependent on direct presentation of antigen the B cells had internalized via the BCR. Here, we used Ag-tg B cells in which peptide transfer to other APCs is prohibited to test whether small precursor numbers of antigen-bearing Fo, MZ, and B-1 B cells can interact with naïve antigen-specific T cells, and if so, what the functional outcome of such an interaction might be.…”
Section: B Cells Also May Be Important In Treg-cell-mediated Supprementioning
confidence: 99%